Edinburgh : festival fears - Mason, Paul, 1967- (London : Macmillan education, 2019)
This is a six-level series of readers for children learning english.
A fact and fiction primary reader, with back-of-book activities and Bilingual Dictionary.
Includes activities and a picture dictionary or wordlist.
Keywords: Juvenile literature; Readers (Primary); English language -- Study and teaching (Primary); Children's books